Decolonizing transness in sport media: the frames and depictions of transgender athletes in Sports Illustrated - Matthews, Tammy Rae, author; Knight Steele, Catherine, advisor; Kodrich, Kris, advisor; Champ, Joseph, committee member; Souza, Caridad, committee member (Colorado State University. Libraries, 2016)
This discourse analysis examines depictions of trans athletes in Sports Illustrated and sport culture through the lens of queer theory and the interpretive-packages model proposed by Gamson & Modiglani (1989). Four interpretive packages emerged from the print content: (1) Marginalization, (2) Labeling, (3) Fighting and Fairness and (4) Pride and Affirmation. The results illustrate that discourse has generally become more sensitive to trans issues. The author presents these results with cautious optimism. Blindingly affirming and romancing the transgender can be equally as superficial as marginalization, and representations of trans athletes secured by one person are problematic. Researchers and sport organizations should dismantle antiquated, coercive sex segregation in traditional sport and decolonize how it contributes to gender-based oppression. The author recommends that media outlets focus on presenting fair, accurate and inclusive representations of transness that combat oppressive positions.